Nest characteristics of stingless bee Heterotrigona itama (Hymenoptera: Apidae) upon colony transfer and splitting - Ahmad Jailani, Nur Maisarah; Mustafa, Shuhaimi; Mustafa, Mohd Zulkifli; Abdul Razak, Mariatulqabtiah (Universiti Putra Malaysia Press, 2019)
Stingless bees are in a diverse group of highly eusocial bees (meliponines) which are reared for their products and pollination potentials. The main source of stingless bee colonies is depending on feral colony hunting that potentially affects the ecosystem. Therefore, establishment of a good practise in colony transfer and splitting may extend the survival of a colony in a new location. This study describes a colony transfer strategy from log to hive and nest characteristics of stingless bee Heterotrigoma itama upon colony splitting from the hive. All 15 colonies from the hollow trunks of trees could survive after one month of transfer to hives. Pre-colony splitting data of 10 daughter colonies showed that the height of brood cells was 14.5 ± 1.20 cm, the number of brood layer was 8.9 ± 2.13, while the number of queen cell was 5.2 ± 1.32. After 12 weeks, the height of brood cells became 16.42 ± 1.05 cm, while the numbers of brood layer and virgin queen eggs were increased to 12.1 ± 1.85 and 6.4 ± 1.65, respectively. However, the correlation between the number of brood layer and virgin queen egg was significantly low (r = 0.421). These results show the ideal strategy for colony transfer from log and colony splitting, and the number of brood layer does not correlate to the presence of virgin queen egg which is crucial for survival of the colony.